Peran Dinas Kesehatan Provinsi Riau Dalam Manajemen Risiko K3 Saat Penanggulangan Kejadian Luar Biasa (KLB) Di Provinsi Riau - Didik Budi Hariyanto; Hetty Ismainar (CV. ITTC INDONESIA, 2025)
The year 2022 was a critical period for Riau Province in managing public health emergencies. According to data from the Riau Provincial Health Office (2022), several outbreaks occurred during this period, including an increase in Dengue Hemorrhagic Fever (DHF) cases in eight districts/cities, a surge in leptospirosis cases in flood-prone areas, and zoonotic rabies incidents in border regions. This study aims to analyze the role of the Riau Provincial Health Office in occupational health and safety (OHS) risk management during outbreak response. Data analysis was conducted using the Fishbone method to identify root causes and the Urgency, Seriousness, and Growth (USG) method to determine problem priorities. Based on the USG assessment, the main priority issue requiring immediate intervention was the unequal availability and distribution of personal protective equipment (PPE) for healthcare workers across affected areas. Interventions for outbreak management in Riau Province in 2022 focused on five components—man, method, money, material, and machine—which were developed based on field analysis. Several factors influencing the implementation of OHS in outbreak management include the availability of PPE, compliance of health workers in using PPE, the implementation of OHS training, and the effectiveness of supervision in applying outbreak response standard operating procedures (SOPs).